Clinical Profile and Outcome of Dilated Cardiomyopathy Children in Banten District Hospital: Retrospective Data of Limited Resources - Amalia Ghanita Herdiana; E.S. Zul Febrianti (CV. Inara, 2026)
Pediatric dilated cardiomyopathy (DCM) is a rare and serious disorder, characterized by left or bilateral ventricular dilatation with impaired systolic function, often leading to heart failure. This retrospective study, conducted at Banten District Hospital in Indonesia, aimed to explore the clinical profile, outcomes, and associated factors in pediatric DCM patients from June 2022 to October 2025. A total of 35 children aged 27 days to 18 years were included. Common comorbidities included rheumatic heart disease, congenital heart disease, tuberculosis, myocarditis, and anemia. The study found a significant relationship between malnutrition and adverse outcomes, with 85.7% of patients surviving, while 14.3% died. The most common ejection fraction (EF) score was moderately reduced (30-40%). These findings underline the importance of addressing underlying comorbid conditions such as rheumatic heart disease and nutritional deficiencies. The study calls for a comprehensive approach to managing pediatric DCM, including early detection and treatment of comorbidities, to improve survival outcomes in resource-limited environments.